Widely targeted metabolomics analysis of Sanghuangporus vaninii mycelia and fruiting bodies at different harvest stages - Qi, Yue; Guo, Xiao-Ying; Xu, Xin-Yue; Hou, Jian-Xuan; Liu, Shi-Lai; Guo, Hong-Bo; Xu, Ai-Guo; Yang, Rui-Heng; Yu, Xiao-Dan (Frontiers in Microbiology, 2024)
Sanghuangprous vaninii is a medicinal macrofungus cultivated extensively in China. Both the mycelia and fruiting bodies of S. vaninii have remarkable therapeutic properties, but it remains unclear whether the mycelia may serve as a substitute for the fruiting bodies. Furthermore, S. vaninii is a perennial fungus with therapeutic components that vary significantly depending on the growing year of the fruiting bodies. Hence, it is critical to select an appropriate harvest stage for S. vaninii fruiting bodies for a specific purpose. With the aid of Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), metabolomics based on ultra-high performance liquid chromatography coupled to triple quadrupole mass spectrometry (UHPLC-QQQ-MS) was used to preliminarily determine 81 key active metabolites and 157 active pharmaceutical metabolites in S. vaninii responsible for resistance to the six major diseases. To evaluate the substitutability of the mycelia and fruiting bodies of S. vaninii and to select an appropriate harvest stage for the fruiting bodies of S. vaninii, we analyzed the metabolite differences, especially active metabolite differences, among the mycelia and fruiting bodies during three different harvest stages (1-year-old, 2-year-old, and 3-year-old). Moreover, we also determined the most prominent and crucial metabolites in each sample of S. vaninii. These results suggested that the mycelia show promise as a substitute for the fruiting bodies of S. vaninii and that extending the growth year does not necessarily lead to higher accumulation levels of active metabolites in the S. vaninii fruiting bodies. This study provided a theoretical basis for developing and using S. vaninii.